PEDAGOGICAL MEASUREMENT OF UKRAINIAN PIANO ART AS A FACTOR OF THE FORMATION OF EXECUTIVE CULTURE OF FUTURE TEACHERS-MUSICIANS - Mihalyuk, Alla (Educological discourse, 2019)
The article is devoted to highlighting the cultural and educational significance of Ukrainian piano art as a means of forming the performing culture of future teachers of musical art. Ukrainian piano art belongs to the achievements of the history of world classical art and is an invaluable source of national musical culture, which has absorbed the features of important achievements of national culture. It is determined that Ukrainian piano art as a component of spiritual culture is a kind of musical and specific form of instrumental art, is a cultural and historical phenomenon, which is based on achievements and mutual influence of performing, pedagogical and creative activity. The peculiarities of the Ukrainian piano art as a cultural and historical phenomenon are expressed in the periodization of the formation and development of piano art in Ukraine, reflected in the interpretive and performing principles of the national piano school, are reflected in the educational and educational principles of playing piano playing on the basis of Ukrainian musical and educational practice. Particular attention is paid to the disclosure of the pedagogical component of Ukrainian piano art. The general tendencies in piano teaching of domestic pianist pedagogues are considered. Principles of playing the piano playing of future teachers-musicians on the basis of Ukrainian musical-educational practice are analyzed. The role of domestic educational practice of pedagogue-pianists in the process of formation of the performing culture of future teachers of musical art is substantiated. The understanding of the essence of the performing culture of the future teacher of musical art as an integrated professional-personal property, which characterizes the high level of mastering of artistic knowledge, musical-performing skills, pedagogical competencies, is expressed in the ability to artistically substantiate and pedagogically expedient interpretation of the content of a musical work and provides in conditions Performing-pedagogical activity of personal professional-creative growth.